2016
DOI: 10.1111/gcb.13316
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of skates and sharks in the North Sea: 112 years of change

Abstract: How have North Sea skate and shark assemblages changed since the early 20th century when bottom trawling became widespread, whilst their environment became increasingly impacted by fishing, climate change, habitat degradation and other anthropogenic pressures? This article examines long-term changes in the distribution and occurrence of the elasmobranch assemblage of the southern North Sea, based on extensive historical time series of fishery-independent survey data. In general, larger species (thornback ray,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
84
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(98 citation statements)
references
References 72 publications
8
84
0
6
Order By: Relevance
“…These are ecologically relevant species as E. marinus has large impacts upon community structuring (Duffy and Hay 2000;Dick et al 2005), and is an important prey species (Leite et al 2014) that can additionally be considered a proxy for other small crustacean species and small fish due to strong swimming behaviours. S. canicula is a generalist benthic predator (Kaiser and Spencer 1994;Domi et al 2005) with high abundances (Genner et al 2010;Sguotti et al 2016) that have been found to increase with increasing temperature (Sguotti et al 2016). S. canicula presents as an ideal indicator species that is not affected by fishing mortality, due to lack of fishing pressure and high discard survival rate (Revill et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…These are ecologically relevant species as E. marinus has large impacts upon community structuring (Duffy and Hay 2000;Dick et al 2005), and is an important prey species (Leite et al 2014) that can additionally be considered a proxy for other small crustacean species and small fish due to strong swimming behaviours. S. canicula is a generalist benthic predator (Kaiser and Spencer 1994;Domi et al 2005) with high abundances (Genner et al 2010;Sguotti et al 2016) that have been found to increase with increasing temperature (Sguotti et al 2016). S. canicula presents as an ideal indicator species that is not affected by fishing mortality, due to lack of fishing pressure and high discard survival rate (Revill et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…De abundantie aldaar is toegenomen in de afgelopen 5 jaar (Walker & Kingma, 2013;Sguotti et al, 2016 Zee, Oostzee, in de periode 1977-2013. Bron: Heessen et al (2015 2.4 Migratie van de stekelrog Er zijn verschillende experimenten uitgevoerd naar de ruimtelijke en temporele verspreiding en eventuele seizoenmigratie van stekelroggen in en rond de Noordzee (Walker et al, 1997;Hunter et al 2005;Chevolot et al, 2006;Humphries et al, 2016 (Hunter et al, 2005).…”
Section: Discussionunclassified
“…Bijvoorbeeld in geval van het sedimenttype prefereren adulte stekelroggen in enkele gebieden, zoals Ierse Zee (Maxwell et al, 2009) en de Middellandse Zee (Lauria et al, 2015), zachte substraten, vooral zand, terwijl dat in andere gebieden zoals de Noordzee (Sguotti et al, 2016) (Walker, 1996;Heessen et al, 2015).…”
Section: Figuur 11 Ruimtelijk Gemiddeld Aanlandingssucces Roggen (Uitunclassified
“…For example, we developed a process-driven characterization of sedimentary habitats for the Basque continental shelf and demonstrated that species richness decreases rapidly with increased sediment resuspension (Galparsoro et al, 2013). Habitat modeling of elasmobranchs in the southern North Sea demonstrated the extirpation of some species such as common skate over time (Sguotti et al, 2016). Modeling spatial distribution of three common seabird species in the southern North Sea demonstrated the importance of habitat type and availability fish prey to seabird distributions (see Lynam et al, 2015a).…”
Section: Habitats and Functionmentioning
confidence: 99%